PERKEMBANGAN KOGNITIF ANAK MELALUI PERMAINAN POHON PINTAR PADA KELOMPOK A (USIA 4-5TAHUN) DI RA RAUDLATUL ULUM KOTALON BATAH TIMUR KWANYAR BANGKALAN - Tri Wahyu Martiningsih; Wardatul Mahmudah (Atthufulah : Jurnal Pendidikan Anak Usia Dini, 2021)
This research is motivated by the low cognitive ability of children in group a. the problem is that there are still many children who have not been able to achieve the indicators of cognitive ability, some children still have difficulty in counting. based on the background of that problem, the problem formulation emerged: how the process of increasing cognitive development through smart tree games in group a. smart tree games can be done by means of children sticking fruit shapes on trees so that children can think when doing these activities and their cognitive development can be further improved. the kind of research used is classroom action research, to find and solve learning problems in the classroom and is carried out cyclically. each cycle consists of planning, action, observation, and reflection with the aim of improving the quality and learning outcomes in the classroom. the results obtained from improving children's cognitive development through smart tree games at ra raudlatul ulum kotalon batah timur kwanyar bangkalan in the first cycle reached 64%, while in the second cycle it reached 85.71% which was able to reach the kkm of a total of 14 students. suggestions that can be given include: the principal must provide the facilities needed by students, such as games, the goal is that children do not feel bored when teaching and learning activities take place. meanwhile, for the teachers is to always encourage their students.